2012
DOI: 10.1002/jpln.201100177
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus forms and enzymatic hydrolyzability of organic phosphorus in soils after 30 years of organic and conventional farming

Abstract: Lower P-input levels in organic than conventional farming can decrease soil total and available P, which can potentially be resupplied from soil organic P. We studied the effect of 30 y of conventional and organic farming on soil P forms, focussing especially on organic P. Soil samples (0-20 cm) were taken in a field experiment with a nonfertilized control, two organic systems receiving P inputs as animal manure, and two conventional systems receiving only mineral P or mineral P and manure. Soils were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 48 publications
(61 reference statements)
3
48
3
2
Order By: Relevance
“…The P budgets were more differentiated, with the only positive budget observed in MI-NORG and the most negative in NON. The P budgets were similar to those shown by Oehl et al (2002) for the period 1978-1998 and by Keller et al (2012) for the period 1978-2007. Based on these P budgets, Oehl et al (2002) reported P transfers between horizons but no significant losses from the profile beyond 50 cm depth.…”
Section: C N P Inputs and Budgets In The Dok Trialsupporting
confidence: 88%
“…The P budgets were more differentiated, with the only positive budget observed in MI-NORG and the most negative in NON. The P budgets were similar to those shown by Oehl et al (2002) for the period 1978-1998 and by Keller et al (2012) for the period 1978-2007. Based on these P budgets, Oehl et al (2002) reported P transfers between horizons but no significant losses from the profile beyond 50 cm depth.…”
Section: C N P Inputs and Budgets In The Dok Trialsupporting
confidence: 88%
“…Phosphatases hydrolyse different phosphate ester bonds to release inorganic P. Therefore, phosphomonoesterases cleave P from monoester forms, such as phospholipids or nucleotides, and phosphodiesterases release P from compounds like nucleic acids (Keller et al 2012;Paul 2015). Since plants secrete phosphodiesterase only under severe P deficiency, the enzyme is mainly produced by microorganisms (Turner and Haygarth 2005).…”
Section: Activities Of Phosphomonoesterase and Phosphodiesterasementioning
confidence: 99%
“…Microbial processes are involved in effective recovery of nutrients from manure and composted organic matter resulting in the release of essential plant nutrients during interactions with soil fauna, including earthworms (Bhadauria & Sazena, 2010). Higher levels of microbial activity in soil under organic managment may not necessarily lead to increased access to stable forms of phosphorus in organic matter (Keller et al, 2012). Re-use of organic 'wastes' (e.g.…”
Section: Examples Of Sources Of Nutrients From Organic Mattermentioning
confidence: 99%